A Fast View-factor Model on Reflection Loss Calculation of Cavity Receiver. (May 2015) - Zhang, Q.Q.; Li, X.; Chang, C.; Liao, Z.R.; Wang, Z.F.; Yu, Q.
Abstract: The reflection energy loss of a cavity receiver is complicated due to the structure of multi-surface inside the cavity. Based on the assumption of semi-gray diffuse reflection, a fast model is proposed to solve the problem. During the calculation, each panel is treated as a semi-gray diffuse reflecting surface. The solar radiation energy transfer between different surfaces is also considered. The fast model is then used to calculate the reflection energy loss of a molten salt cavity receiver with known view factors. The result is compared with values calculated through other models, and the fast model is proved effective to calculate the reflection energy loss of cavity receivers.